Scripted Computer-Supported Collaborative Writing : University Students’ Insights on Enabling and Hindering Factors - Syynimaa, Kirsi; Lainema, Kirsi; Hämäläinen, Raija; De Wever, Bram (ISTES Organization, 2025)
The focus of the present study is to investigate university students' views on the scripted computer-supported collaborative writing method. The study presented in this article was conducted at one Finnish university and one Belgian university. A total of 91 university students were randomly assigned to small groups of three to five members. All groups were instructed to follow a four-phase simultaneous sequential integrating construction script for their collaborative writing task. The inductive thematic analysis of the students' reflective essays indicated a variety of factors that either enabled or hindered computer-supported collaborative writing within the scripted learning context. Four main themes were captured: individual, group, script, and activity-based factors. Furthermore, our findings suggest that students specifically identified enabling factors as group-based, such as collaboration or effective communication between group members. Conversely, the data revealed that the hindering factors were especially script-based, such as students expressing confusion about the script or how to approach the collaborative writing task. These findings have practical implications for the design of scripted joint writing activities in computer-supported settings in higher education.